Estimation of Runoff by applying SCS Curve Number Method, in a complex arid area; Wadi Al-Mujib watershed; Study case - Alzghoul, Maysoon; Al-husban, Yusra (Dirasat: Human and Social Sciences, 2021)
Geographic information system (GIS), and the advance application of Remote Sensing (RS) techniques were used to estimate surface runoff in combination with the SCS-CN method in a complex arid area; Wadi Al-Mujib watershed. The runoff curve number (CN) is a key factor in determining runoff in the SCS (Soil Conservation Service) based hydrologic modeling method. This paper assesses the modeling of flow in a complex canyon arid area of Wadi Al-Mujib watershed; with historical annual rainfall ranging between <50 mm in most of the study area to 500 mm in the western mountain part. The SCS-CN is a quantitative description mainly controlled by the main factors; soil hydrologic groups (SHGs), rainfall data (P), land use /Land cover patterns (LULC), antecedent moisture condition (AMC) and Potential Maximum Retention (S). SCS–CN method based on remote sensing and GIS data as inputs and median of ordering data for all the three antecedent moisture conditions (AMC I, AMC II and AMC III) is used. For estimation the runoff, four storm events within sixteen days were selected in the years of 2010/2011,witen 20 days, 2015/2016 and 2016/2017,witen 25 day which represents the three moisture conditions, drought, wet, and normal conditions (AMC-I, AMC-II and AMC-III). The analysis indicated that there is a strong correlation between the CN values obtained from measured runoff and the rainfall depth. The result showed that 89.3% from the total area of Wadi Al-Mujib watershed under high CN value, which interprets in high runoff to the Wadi Al-Mujib watershed, as the most prominent of LULC were barren area 98.67% from the total area of Wadi Al-Mujib watershed. The total calculated runoff volume were 0.23, 1.97, and 19.09mm³ for the three moisture conditions, drought, normal and wet conditions, respectively. The present study reveals that SCS-CN method with integration of GIS and remote sensing technology can effectively be used to estimate the runoff in many an ungauged desert watershed in Jordan.